Between uncertainty and destiny: the patient journey in axial spondyloarthritis care from the perspectives of patients and their relatives - Susann May; Greta Nordmann; Franziska Gabb; Katharina Boy; Magali Wagner; Niklas Ohm; Hanna Labinsky; Johannes Knitza; Sebastian Kuhn; Martin Heinze; Martin Welcker; Felix Muehlensiepen (BMC Rheumatology)
Abstract Axial spondyloarthritis (axSpA) is an inflammatory rheumatic disease primarily affecting the sacroiliac joints and spine, leading to chronic pain, fatigue, and reduced mobility. The diagnostic delay for axSpA is often long, causing significant physical, psychological, and social burdens for patients and their relatives. This study aims to explore the patient journey of individuals with axSpA and their relatives within the German healthcare system, identifying key challenges and unmet needs from symptom onset to diagnosis and treatment. A qualitative approach was employed, involving structured interviews with axSpA patients and their relatives. Participants were selected through purposive sampling to ensure diverse representation. Data collection involved individual telephone interviews, which were transcribed and analyzed using Kuckartz’s structured qualitative content analysis framework. The patient journey was characterized by four distinct phases: Time before diagnosis, Diagnosis, After the diagnosis, and Current treatment. Participants reported significant psychological and emotional burdens, with many experiences attributed to chance encounters with knowledgeable healthcare professionals. Key issues included a lack of awareness among healthcare professionals, diagnostic delays, and inadequate psychological support. The perspectives of patients and their relatives highlighted the significant psychological burden they both experience throughout the journey. This underscores the need for services that cater not only to patients but also to their relatives. The study highlights critical gaps in the current healthcare system regarding the diagnosis and care of axSpA patients. To improve care, systematic efforts are needed to enhance awareness, reduce diagnostic delays, integrate psychological support, and provide comprehensive information throughout the patient journey for both, patients and relatives. Effective care should not rely on chance; systematic improvements are necessary to ensure consistent, high-quality care.